PENGARUH MOTIVASI DAN DISIPLIN TERHADAP KINERJA PETUGAS PEMASYARAKATAN DI RUMAH TAHANAN NEGARA KLAS I SURAKARTA - ETYKAWATY, RIANA (2005)
This research has a title of "The influence of Motivation and Discipline to the working performance in the staff of the Surakarta's first class state penitentiary. The objective of this research is to find the existence of the influence of motivation and discipline to the working performance of the staffs both collectively and individually. This research used data in the form of questionnaires given to 110 respondents, which is the working staffs itself. Data analysis used validity test and questionnaire reliability. The results is tested using the double regression analysis with parameter test, model precision test and classic assumption test. The validity and reliability test stated that the given questionnaires is valid and reliable. Data analysis results shown that motivation variable gave positive score to the increase of staff's peformance, whether discipline variable also gave positive score to the increase of staff's performance in Surakarta's first class state penitentiary. Model acquirement is stated as precise and un-biased because there are no problem in the classic assumption test and model precision test. The F-test and T-test state that motivation and discipline variable has a significant and positive impact to the staff's performance variable. From the result analysis it can be concluded that motivation and discipline has a positive and significant impact to the performance of the working staff in Surakarta's first class state penitentiary.